Community Participation Arrangements to Prevent Illegal Drilling - Iza Rumesten, R.S.; Febrian Febrian; Helmanida Helmanida; Agus Ngadino (Faculty of Law, Hasanuddin University, 2018)
The practice of illegal drilling does not only result in destruction for to the environment, but also result in the social gap, national losses, and people’s lives. It happens to illegal drilling conducted manually using traditional equipment and less operational standard. This illegal drilling may happen because ineffective law applied and no regulation on social participation in the Law of oil and natural gas. This research uses the normative method, the result of research is analyzed qualitatively. The research showed that the active social participation was needed in environmental law enforcement to prevent a great number of illegal drilling practice, the higher level of social participation in environmental law enforcement, and the smaller illegal drilling practice could be. Thus, there must be any act arranging for social participation in enforcing the environmental law arranged in the law No. 22 of 2001 because of those the local societies who get the direct effect of environmental destruction as a result of drilling of oil and natural gas illegally.